Philolaus of Croton, On Nature (Περὶ φύσεως). Doxography and Fragments - Wesoły, Marian Andrzej (Wydział Filozoficzny UAM, 2022)
The present article consists of two parts. First, we provide some general information on the life and views of Philolaus. This serves as an introduction to the second part which offers a new Polish translation of the most important ancient testimonies on Philolaus and the preserved fragments from his book On Nature (the latter are quoted along with the Greek original). According to the most recent research, these fragments are authentic and give an important insight into the Pythagorean and early Greek philosophy. The present selection of Philolaus’ testimonies and fragments has been arranged in a novel and accessible manner.
Filolaos z Krotony,O naturze (Περὶ φύσεως) doksografia i fragmenty
Keywords: Philolaus; authentic; fragments; peri physeos; historia; new Polish translation